Seventeenth century men of latitude;: forerunners of the new theology - George, Edward Augustus (C. Scribner's sons, 1908)
Men of latitute in a century of narrowness.--John Hales.--William Chillingworth.--Benjamin Whichcote.--John Smith.--Henry More.--Jeremy Taylor.--Sir Thomas Browne.--Richard Baxter.--Conclusion.